Validação de conteúdo do diagnóstico de enfermagem Náusea - Pompeo, Daniele Alcalá; Rossi, Lídia Aparecida; Paiva, Luciana (Revista da Escola de Enfermagem da USP, 2014)
This study aimed to evaluate the content validity of the nursing diagnosis of nausea in the immediate post-operative period, considering Fehring’s model. Descriptive study with 52 nurses experts who responded an instrument containing identification and validation of nausea diagnosis data. Most experts considered the domain 12 (Comfort), Class 1 (Physical Comfort) and the statement (Nausea) adequate to the diagnosis. Modifications were suggested in the current definition of this nursing diagnosis. Four defining characteristics were considered primary (reported nausea, increased salivation, aversion to food and vomiting sensation) and eight secondary (increased swallowing, sour taste in the mouth, pallor, tachycardia, diaphoresis, sensation of hot and cold, changes in blood pressure and pupil dilation). The total score for the diagnosis of nausea was 0.79. Reports of nausea, vomiting sensation, increased salivation and aversion to food are strong predictors of nursing diagnosis of nausea.